Pranata Perkawinan dalam Agama Islam dan Kristen; Sebuah Studi Komparatif Integratif - Moch. Nurcholis (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2016)
Not been much found a study evaluating the comparative-integrative among one religion to another religion related regulation of marriage are sourced directly from the scriptures respective religion, in particular Islam and Christianity. This is to give a balanced understanding and response to gender issues, social inequality relation of husband and wife is exhaled by Western scholars-Christians who are quite a lot of cornering the teachings of Islam. Starting from this idea authors conducted research using descriptive-analytic method to then compare giving rise similarities and differences to material for further research. The study concluded that marriage in Islam can be said to have a double dimension; vertical and horizontal dimensions, whereas the more dominant Christian vertical dimension though there is also a horizontal dimension, as well as striking differences more visible on the issue of legal origin of marriage, polygamy, the permanence of marriage and the problem of intermarriage